(untitled) (ModaPalavra e-periódico, 2019)
This paper sponsored by the Coordination for the Improvement of Higher Education Personnel (CAPES Brasil), we have investigated the relation of art, fashion and museums using an concrete empirical experience. We present the identification of Italian creative strategies of our contemporaneity, under the aspect of sociology, strategy studies and design. Therefore, to offering the knowledge base for professionals and students in art, in communication, and in international creative trade and jewelry design. It was also possible to demonstrate that it satisfies the luxury market with the binomial art-fashion of mutual appreciation as the experience of the Bardini Museum and Marco Baroni jewellery.